PENGARUH CORPORATE SOCIAL RESPONSIBILITY, KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PROFITABILITAS PERUSAHAAN - Wismandana, Nicho Budi; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test whether the effect of corporate social responsibility, managerial ownership and institutional ownership to company profitability. Method of data collection is purposive sampling method from a secondary data source for 3 years, ie 2011-2013 on the Stock Exchange, so that the samples used in this study as many as 15 companies in the three-year study period, the samples used in this study as many as 45 firm years. The results showed that the disclosure of CSR and institutional ownership has an effect on the profitability of the company, while the managerial ownership does not affect the profitability of the company, because of the managerial ownership is too low so that the performance of managers in managing the company less than optimal and managers as a minority shareholder has not been able to actively participate in making a decision in the company, so it does not affect the profitability of the companyKeywords: Corporate Social Responsibility (CSR), Managerial Ownership, Institutional Ownership, Profitability of the Company